EVALUATION OF ARTERIAL PRESSURE CHANGES IN PATIENTS UNDERGOING EXTRACTION OF IMPACTED THIRD MOLARS AND INTRAVASCULAR LASER BLOOD IRRADIATION (CIPEEX, 2025)
The aim of this study was to evaluate and compare the blood pressure of patients who underwent extraction of impacted lower third molars and underwent modified intravascular laser blood irradiation (ILIB) or placebo. Eighteen individuals were allocated into two groups, the Placebo group (n=8) and the ILIB group (n=10). In the Placebo group, low-power laser equipment (InGaAlP) was used, coupled with a bracelet (LaserDuo, MMOptics Equipamentos, São Carlos, Brazil), worn on the wrist of one of the research participants, over the radial artery, but without irradiation. In the ILIB group, the laser was positioned in the same way, but in this case, the laser was irradiated. Both groups underwent a 30-minute treatment. Systolic and diastolic blood pressure were assessed at two time points: before the ILIB session and 4 minutes after local anesthesia. The placebo group showed a positive variation in systolic and diastolic blood pressure, while in the ILIB group a reduction was observed; however, this difference was not statistically significant. The findings suggest that ILIB may help reduce and better control blood pressure in patients undergoing third molar extraction; however, studies with a larger number of patients are needed.
Keywords: Laser Therapy; Low-Intensity Light Therapy; Third Molar; Blood Pressure